Group heterogeneity and social validation of everyday knowledge: The mediating role of perceived group participation - Vala, J. (2014)
Studies presented in this article show that participants attribute greater validity to opinions supported by heterogeneous groups than by homogeneous ones, that this effect occurs whether participants anticipate group belonging or not and that the relationship between heterogeneity and the attribution of validity to opinions is mediated by the perception of participation within heterogeneous groups. More specifically, an experimental scenario was tested in a pilot study (N = 299): group heterogeneity was manipulated and perceived group participation as well as perceived validity of group opinions was measured. Results show the expected effect of heterogeneity on the validation of opinions and also a mediating effect of perceived participation. The main study (N = 336) shows that the effect of heterogeneity occurs not only when participants are mere observers of groups but also when they anticipate group belonging. Furthermore, this study shows that whereas the effect of group heterogeneity was mediated by perceived participation, the effect of group belonging on perceived validity of group opinions was mediated by trust.